Methods and application for water holdup calculation and flowing image based on array electromagnetic wave instrument in horizontal water-oil wells - CHEN Meng,XIE Weifeng,ZHANG Yu,YANG Guofeng,LIU Xiangjun (Youqicang pingjia yu kaifa)
The accurate calculation of the water holdup and the inversion of fluid distribution for multi-phase flow play a crucial role in understanding the development performance in horizontal wells. This study builds upon the array electromagnetic wave holdup instrument and proposes a novel method for calculating water holdup. The method is based on the weight of the mid-point tangential area of the probe's radial projection. Additionally, inversion methods for oil-water phase distribution in horizontal wells, considering high, middle, and low water content, were developed by comparing them with existing quantitative calculation methods of the array holdup instrument. The results demonstrated that the new method exhibited an average absolute error of 4.43 % and relative errors of 16.34 %. These values were significantly better than those obtained using the weight coefficient method and the radial contour area method. For the inversion of fluid distribution in horizontal wells with high, middle, and low water cut conditions, the Gaussian Radial Basis method and multivariate linear method provided the best matches. This research lays a solid foundation for evaluating the production performance of multi-phase flow in horizontal wells.